Composite Materials and Processing. - Balasubramanian, M. (Taylor and Francis, 2013)
Composite Materials and Processing provides the science and technology of processing several composites using different processing methods, and includes collective information on the processing of common and advanced composite materials. It also weighs the advantages and disadvantages of various processing methods. This book is suitable for materials scientists, and graduate students, as well as for practicing engineers in composite industries. The book describes the basis for the performance of different reinforcements and matrix materials, highlights technolo.